1990
DOI: 10.1111/j.1438-8677.1990.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle changes during callus initiation from cultured maize embryos. An autoradiographic study

Abstract: Cell cycle changes were examined in various scutellar regions of immature maize embryos during a total culture period of72 h on a modified MS agar medium containing I mg 1-1 2,4-0 and 6% sucrose. At intervals of 8 h embryos were sampled and transferred to the MS medium supplemented with 5~Ci ml-I [,H]thymidine and incubated for 8 h. The fraction oflabelled nuclei was determined for each interval and a comparison was made between the scutellar regions. During the first day, identical changes in the fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…2,4-D is able to cause various irregularities in cells cultivated in vitro (Bayliss 1980, Ager et al 1991, Pavlika et al 1991. The mutagenic influence of 2,4-D takes place as unorganized rapid cell growth (Karp 1991) and depends on the genotype (Fransz et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…2,4-D is able to cause various irregularities in cells cultivated in vitro (Bayliss 1980, Ager et al 1991, Pavlika et al 1991. The mutagenic influence of 2,4-D takes place as unorganized rapid cell growth (Karp 1991) and depends on the genotype (Fransz et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In both inbreds, the 1st day of culture is characterized by cytologic changes, such as an increase in the number of organelles, and changes in vacuolation and nuclear morphology. Determination of the incorporation of [ 3 H]thymidine in the scutellum showed that the lines had similar mitotic indexes (Fransz et al 1990). This early phase is called the shock response phase, and aforementioned characteristics also occur in the absence of 2,4-D Schel 1987, 1991).…”
mentioning
confidence: 99%